Dealing with diversity - An honors program for students of teacher training starting in Muenster - Christian Fischer; Julia Gillhaus; David Rott; Vivian van Gerven (Hanze UAS, 2017)
Dealing with diversity is a main topic in teacher education in Germany. One aspect which is often inadequately represented is gifted education in this context. Often dealing with diversity starts with a negative point of view: which difficulties does the student have? Another point of access in classroom could be a focus on the individual potentials. The idea of giftedness and talents gives another point of view to this topic. First a short overview about Giftedness and Learning is given. The leading idea of diversity in school is following. With the Challenge and Support Project, a best practice example is given for illustration.